Changes in grammage, tearing resistance, and water vapor transmission rate of active paper incorporated with Cinnamaldehyde during storage at various temperatures. Issue 1 (January 2016) - Manuhara, G J; Khasanah, L U; Utami, R
Abstract: Antimicrobial properties of active paper packaging incorporated with cinnamaldehyde and its application in the storage of agricultural products had been studied. However, changes in grammage, tear resistance and water vapor transmission rate (WVTR) of the active paper during storage is not yet known, whereas it is important to provide consideration in application of the active paper. This study aims to determine the changes in those physical properties during storage (20 days) at various temperatures (10, 20, 25, 30, and 40 °C). The grammage and WVTR of the active paper decreased as increase in storage time and temperature, while the tearing resistance increased as storage time. Higher temperature caused slower increase in tearing resistance, but the results showed fluctuation. The results of Arrhenius plot indicated the activation energy (in kJ/mol) of those physical properties, sorted from the highest to the lowest as follows: 53.6 (grammage), 14.8 (WVTR) and 13.8 (tearing resistance).